Trade-Offs and Synergies Between Ecosystem Services and Their Ecological Security Patterns in the Guanzhong–Tianshui Economic Zone - Jing Zhou; Jianhua Xiao; Daiying Yin; Yu Ren (Land)
The Guanzhong–Tianshui economic zone is a strategic link in China’s Belt and Road network, faces the contradiction between ecological protection and economic development, and urgently needs to construct an ecological security pattern based on ecosystem services to permit sustainable development. In this study, we evaluated the ecological services of net primary productivity (NPP), water yield (WY), soil conservation (SC), habitat quality (HQ), and food production (FP). We explored the trade-offs and synergies between services using correlation analysis and geographically weighted regression and constructed an ecological security pattern through circuit theory. NPP, WY, SC, and FP increased during the study period, whereas HQ decreased. The NPP × WY, WY × SC, and WY × HQ shifted from synergies to trade-offs; NPP × SC, NPP × HQ, and SC × HQ were always synergies; NPP × FP, SC × FP, and FP × HQ were always trade-offs; and WY × FP shifted from trade-offs to synergies. We selected service bundles with significant synergies among NPP, SC, and HQ as ecological sources, which were mainly in the Qinling and Weibei mountains, comprising 47 ecological patches. We identified 58 ecological corridors, 330.83 km2 of pinch points, and 401.30 km2 of barriers, which form a mesh structure covering the study area, proposing a development pattern of six zones and one belt. Our results provide a framework for ecological protection and restoration, which may serve as a scientific foundation for upcoming regional land management initiatives.